Prophylactic cranial irradiation in resected early stage small cell lung cancer: an updated systematic review and meta-analysis - Ze Yuan; Dan Tao; Dingyi Yang; Yong Jiang; Erha Munai; Siwei Zeng; Zhiying Zhou; Wei Zhou; Yongzhong Wu (Radiation Oncology)
Abstract Background The use of prophylactic cranial irradiation (PCI) in early stage small cell lung cancer (SCLC) patients post-surgery remains controversial. This meta-analysis aimed to evaluate the efficacy of PCI in resected early stage SCLC patients. Methods Relevant literature was reviewed through PubMed, Cochrane, and Embase databases. The pooled hazard ratios (HRs) for overall survival (OS) were analyzed for the overall population, as well as for pathologically node-negative (pN0) and pathologically node-positive (pN+) patients. We also assessed the pooled HRs for brain metastasis-free survival (BMFS) in all patients. Sensitivity analyses were conducted to validate these results. Results A total of 13 retrospective studies were included, encompassing 3,530 postoperative SCLC patients, of whom 880 received PCI treatment. In the overall patient population, PCI significantly improved OS compared to non-PCI group (HR: 0.66, 95% CI 0.58–0.74, p < 0.001). For pN0 patients, there was no significant OS benefit from PCI (HR: 0.85, 95% CI 0.65–1.10, p = 0.22). In contrast, pN + patients showed a significant OS improvement with PCI (HR: 0.52, 95% CI 0.41–0.66, p < 0.001). Furthermore, PCI significantly improved BMFS in all patients (HR: 0.42, 95% CI 0.29–0.60, p < 0.001). Sensitivity analyses confirmed the stability of these results. Conclusions PCI was associated with a significant improvement in OS and BMFS in resected early stage SCLC patients. The benefits of PCI were particularly pronounced in pN + patients, whereas pN0 patients did not experience a significant OS benefit. These findings supported the selective use of PCI based on nodal status to optimize treatment outcomes in postoperative SCLC patients.